Self-Management: A New Eight-Minute Stretching Program for Employees with Musculoskeletal Disorders (MSDs) - Siti Latipah; Shieva Nur Azizah Ahmad (Jurnal Keperawatan Indonesia, 2024)
Musculoskeletal disorders (MSDs) are the main cause of workplace injuries. MSDs are health problems that attack the body’s propulsion systems, such as muscles, tendons, ligaments, joints, cartilage, and nerves. This study aims to determine the effectiveness of Self-Management: A New Eight-Minute Stretching Program against MSDs in a company X, Tangerang, Indonesia. A quantitative, quasi-experimental research method using a non-equivalent control group pre-test-post-test design was conducted on 90 respondents, who were divided into two sample groups by using side probability with a simple random sampling technique. The MSD risk measurement instrument used the Nordic Musculoskeletal Questionnaire. The results obtained showed that the majority of respondents were adults (51.3%), male (67.2%), and had more than three years of working experience (43.7%). The results of a Mann–Whitney U test found that there were differences in the level of complaints about MSDs between the intervention group and the control group (p = 0.00). However, using Wilcoxon, there were differences in complaints about MSDs during the pre-test and post-tests (p = 0.00). Based on the research results, it is suggested that every company provide continuous education to employees so that they can implement this program independently while working or at home. This prevention can reduce complaints of MSDs, so that, together with reduced complaints, the quality of health will improve. Keywords: effectiveness, employees, musculoskeletal disorders   Abstrak Manajemen Diri: A New Eight-Minute Stretching Program terhadap Musculoskeletal Disorders (MSDs) pada Karyawan. Musculoskeletal disorder (MSDs) merupakan penyebab utama kecelakaan di tempat kerja. MSDs adalah masalah kesehatan yang menyerang sistem alat penggerak tubuh, seperti otot, tendon, ligamen, sendi, kartilago dan saraf. Penelitian ini bertujuan untuk mengetahui efektivitas Manajemen Diri: A New Eight Minute Stretching Program terhadap Musculoskletal Disorders (MSDs) pada karyawan di perusahaan X, Tangerang, Indonesia. Penelitian ini menggunakan desain kuantitatif dengan metode quasi-experimental menggunakan non-equivalent control group pre-test-post-test design terhadap 90 responden yang terbagi menjadi dua kelompok sampel. Pengambilan sampel menggunakan side probability dengan teknik simple random sampling. Instrumen pengukuran risiko MSDs menggunakan kuesioner the Nordic Musculoskeletal. Hasilnya didapatkan mayoritas responden berusia dewasa (51,3%), laki-laki (67,2%), lama kerja lebih dari tiga tahun (43,7%). Hasil dari uji Mann Whitney ditemukan perbedaan tingkat keluhan MSDs antara kelompok intervensi dan kelompok kontrol (p = 0,00); sedangkan dengan menggunakan uji Wilcoxon ditemukan perbedaan keluhan MSDs saat pre-test dan post-test (p = 0,00). Berdasarkan hasil penelitian disarankan setiap perusahaan memberikan edukasi pada karyawan secara kontinu untuk menerapkan program ini secara mandiri saat bekerja ataupun di rumah. Program ini dapat mengurangi keluhan MSDs, seiring dengan berkurangnya keluhan tersebut maka kualitas kesehatan akan meningkat. Kata Kunci: efekititas, karyawan, muskuloskletal disorders